M2SR, a novel live single replication influenza virus vaccine, provides effective heterosubtypic protection in mice. Issue 42 (30th September 2016) - Sarawar, Sally; Hatta, Yasuko; Watanabe, Shinji; Dias, Peter; Neumann, Gabriele; Kawaoka, Yoshihiro; Bilsel, Pamuk
Highlights: M2SR is anM2 -deletedS ingleR eplication novel influenza vaccine. M2SR provides homosubtypic and heterosubtypic protection in mice. M2SR elicits cross-reactive T cell responses recalled upon heterosubtypic challenge. Abstract: Despite the annual public health burden of seasonal influenza and the continuing threat of a global pandemic posed by the emergence of highly pathogenic/pandemic strains, conventional influenza vaccines do not provide universal protection, and exhibit suboptimal efficacy rates, even when they are well matched to circulating strains. To address the need for a highly effective universal influenza vaccine, we have developed a novel M2-deficient single replication vaccine virus (M2SR) that induces strong cross-protective immunity against multiple influenza strains in mice. M2SR is able to infect cells and expresses all viral proteins except M2, but is unable to generate progeny virus. M2SR generated from influenza A/Puerto Rico/8/34 (H1N1) protected mice against lethal challenge with influenza A/Puerto Rico/8/34 (H1N1, homosubtypic) and influenza A/Aichi/2/1968 (H3N2, heterosubtypic). The vaccine induced strong systemic and mucosal antibody responses of both IgA and IgG classes. Strong virus-specific T cell responses were also induced. Following heterologous challenge, significant numbers of IFN-γ-producing CD8 T cells, with effector or effector/memory phenotypes and specific for conserved viral epitopes, were observed in the lungs of vaccinated mice. A substantial proportion of the CD8 T cells expressed Granzyme B, suggesting that they were capable of killing virus-infected cells. Thus, our data suggest that M2-deficient influenza viruses represent a promising new approach for developing a universal influenza vaccine.